Thomas Annan of Glasgow Pioneer of the Documentary Photograph - Gossman, Lionel (Open Book Publishers, 2015)
In the wake of Glasgow's transformation in the nineteenth-century into an industrial powerhouse, the "Second City of the Empire," a substantial part of the old town of Adam Smith degenerated into an overcrowded and disease-ridden slum. The Old Closes and Streets of Glasgow, Thomas Annan's photographic record of this central section of the city prior to its demolition in accordance with the City of Glasgow Improvements Act of 1866, is widely recognized as a classic of nineteenth-century documentary photography. Annan's achievement as a photographer of paintings and a portrait and landscape photographer is less widely known. Thomas Annan: Photographer of Victorian Scotland offers a handy, comprehensive and copiously illustrated overview of the full range of the photographer's work. The book opens with a brief account of the immediate context of Annan's career as a photographer: the astonishing florescence of photography in Victorian Scotland. Successive chapters deal with each of the main fields of his activity, touching along the way on issues such as the nineteenth-century debate over the status of photography - a mechanical practice or an artistic one? - and the still ongoing controversies surrounding the documentary photograph in particular. While the text itself is intended for the general reader, extensive endnotes amplify particular themes and offer guidance to readers interested in pursuing these themes further.